Case report: Spontaneous coronary artery rupture presenting with acute coronary syndrome: A rare diagnosis of common disease - Sayed, Ahmed Ibrahim (Frontiers in Cardiovascular Medicine, 2022)
Acute coronary syndrome (ACS), myocardial infarction, and sudden death have all been linked to spontaneous coronary artery rapture (SCAR). Patients primarily afflicted by SCAR are those with or without cardiovascular risk factors, notably men, implying a mechanism distinct from the more prevalent atherosclerosis. Both medical and interventional treatment should consider the diverse causes of ACS as well as the patient's clinical stability. I herein report an unusual case of a 33 years old male who presented with acute chest pain to the emergency department. His physical exam was normal. The electrocardiogram showed non-specific ST segment changes in anterior leads, and the echocardiogram revealed mild anterior wall hypokinesia with no evidence of pericardial effusion. He underwent coronary angiography which revealed a contained rupture in the anterior descending coronary artery. The patient underwent uneventful lifesaving coronary artery perforation repair. It concluded that, though rare, SCAR should be considered as a differential diagnosis in patients with ACS, even in the absence of pericardial effusion in adult patients of all ages.